Chronic toxicity of parabens and their chlorinated by‐products in Ceriodaphnia dubia. Issue 6 (27th December 2013) - Terasaki, Masanori; Abe, Ryoko; Makino, Masakazu; Tatarazako, Norihisa
ABSTRACT The chronic toxicity of 12 compounds of parabens and their chlorinated by‐products was investigated using 7‐day Ceriodaphnia dubia test under static renewal condition in order to generate information on how to disinfect by‐products of preservatives that are discharged in aquatic systems. The mortality and inhibition of reproduction tended to increase with increasing hydrophobicity and decreased with the degree of chlorination of parabens. The EC50 values for mortality, offspring number, and first brood production ranged between 0.30–3.1, 0.047–12, and 1.3–6.3 mg L−1, respectively. For the number of neonates, the most sensitive endpoint, the no‐observed‐effect concentration (NOEC) and lowest‐observed‐effect concentration (LOEC) values ranged from 0.63 to 10 mg L−1 and from 1.2 to 19 mg L−1, respectively. Methylparaben (MP), benzylparaben (BnP), and dichlorinated BnP (Cl2BnP) elicited a significant decrease in offspring numbers even at their lowest concentration tested; the NOEC for these compounds was determined to be less than the lowest test concentration (1.3, 0.04, and 0.63 mg L−1 for MP, BnP, and Cl2BnP, respectively). Propylparaben (PP), chlorinated PP, isopropylparaben (iPP), and chlorinated iPP exhibited nonmonotonic concentration‐dependent response; their NOEC and LOEC values could not be determined. The multivariate approach involving principal component analysis and hierarchical cluster analysis revealed four groups that corresponded to the toxicological profiles of parabens. Our results suggested that disinfection of parabens by chlorination could reduce aquatic toxicity of original compounds. The findings obtained in our study together with the data available on paraben concentrations in aquatic systems can be used to perform preliminary risk assessment by comparing the predicted environmental concentration (PEC) with the predicted no‐effect concentration (PNEC) for the marine aquatic environment. The calculated PEC/PNEC ratios ranged from 0.0012 to 0.2, with the highest value observed in MP. This suggested that there are negligible environmental risks for aquatic organisms at current use levels. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 664–673, 2015.